Assessing Suicidal Ideation in a Community of Bangladesh: Validation of a Suicidal Ideation Scale - Md Omar Faruk; Md Abdul Awal; Kamal Uddin Ahmed Chowdhury (Indian Journal of Psychological Medicine, 2026)
Background: Surpassing the global and Bangladesh averages, Jhenaidah, a southwestern region in Bangladesh, remains one of the most prone districts for suicidal ideation and suicide rates. However, despite the higher prevalence, there is no psychometric measure available to assess the degree of suicidal ideation in this region. The present study aimed to validate the Bangla version of the Suicidal Ideation Scale (B-SIS) in Jhenaidah. Methods: We recruited 300 participants (male 50.87% and female 45.13%) via purposive sampling from six sub-districts, with an overall mean age of 23.26 (SD = 2.96). We used the B-SIS, the World Health Organisation-5 Well-being Index and the Symptom Rating Scale. Results: The scale yielded a one-factor structure with 55.58% of the total variance supported by multiple indices in confirmatory factor analysis (RMSEA = 0.061, CFI = 0.981, TLI = 0.971, SRMR = 0.035). The intraclass correlation coefficient (two-way random-effects model, absolute agreement) for average measures was 0.90 (95% CI, [0.84, 0.95]; F [29, 551] = 10.11; p < .001), indicating high score stability across administrations. The scale also demonstrated acceptable internal consistency, reliability and construct validity. Conclusions: The psychometric properties suggest that the B-SIS is a suitable measure to assess suicidal ideation in Jhenaidah. The study is expected to advance scholarly work in suicidology by taking Jhenaidah into account.